2019
DOI: 10.14198/medcom2019.10.1.6
|View full text |Cite
|
Sign up to set email alerts
|

La gamificación en la universidad española. Una perspectiva educomunicativa

Abstract: Los estudiantes están creciendo en una sociedad tecnificada y, por ello, desarrollan distintas capacidades cognitivas que resulta imprescindible comprender y atender. Esta realidad ha obligado a los educadores a reconfigurar sus estrategias pedagógicas para una audiencia en la que los alumnos son prosumidores. El objetivo nuclear del estudio nos ha obligado a indagar cómo los docentes de las universidades españolas perciben y aplican el método del juego en sus clases para obtener óptimos resultados en la enseñ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
0
7
0
7
Order By: Relevance
“…Several authors have indicated how integrating ICTs in education promotes healthy development [ 30 , 31 ], including the self-perception [ 9 , 32 ]. In this context, new active methodologies and pedagogical strategies focused on ICTs, mainly serious games in science, technology, engineering, and mathematics (STEM), improve the motivation and self-esteem of students [ 33 , 34 , 35 ].…”
Section: Social and Sustainable Development Gamification And Healthmentioning
confidence: 99%
“…Several authors have indicated how integrating ICTs in education promotes healthy development [ 30 , 31 ], including the self-perception [ 9 , 32 ]. In this context, new active methodologies and pedagogical strategies focused on ICTs, mainly serious games in science, technology, engineering, and mathematics (STEM), improve the motivation and self-esteem of students [ 33 , 34 , 35 ].…”
Section: Social and Sustainable Development Gamification And Healthmentioning
confidence: 99%
“…There are multiple circumstances that have channeled the promotion of video game production in the last decade. First, for Dezuanni (2010) the computer skills incorporated in the so-called technological literacy have provided the generation of knowledge aimed at the development and implementation of new technologies (Peñalva et al 2019), including digital programming and animation; likewise, the progressive access to Internet has reduced inequality gaps and generated a greater field of opportunities and experiences, thus preparing young people in the production of video games (Jenkins 2009). Also, restructuring high schools, museums, community centers, and libraries by adding computers and audiovisual equipment has facilitated the production of video games (Torres-Toukoumidis et al 2017).…”
Section: Production Of Videogamesmentioning
confidence: 99%
“…• -Socialblade: Esta web proporciona una gran variedad de datos incorporando información gamificado mediante insignias y rankings (Peñalva, Aguaded & Torres-Toukoumidis, 2019). Entre los datos iniciales que incluye se encuentran el número de videos cargados, suscriptores, visualizaciones totales, país, tipo de canal y año de creación del canal.…”
Section: Softwares Especializados De Investigación Vinculados a Youtubeunclassified